Implications of Demographic, Religious, and Enrollment Trends for the Footprint of Faith-Based Schools Globally - Wodon, Quentin (The review of faith & international affairs, 2019)
Faith-based schools play an important role today in the provision of education globally. Are the schools likely to continue to play such a role in the future? If so, where is that role likely to be most prominent? This paper considers these questions on the basis of long-term demographic, religious, and school enrollment trends. The trends suggest that enrollment in faith-based schools will continue to grow rapidly, as has been the case over the last few decades. But there will also be a fundamental shift, with a rising concentration of students in faith-based schools located in Africa. This may have implications given the learning crisis affecting the continent.